2013
DOI: 10.2341/12-211-l
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of Teeth Restored With All-ceramic Inlays and Onlays: An In Vitro Study

Abstract: Fracture resistance of inlays and onlays may be influenced by the quantity of the dental structure removed and the restorative materials used. The purpose of this in vitro study was to evaluate the effects of two different cavity preparation designs and all-ceramic restorative materials on the fracture resistance of the tooth-restoration complex. Fifty mandibular third molar teeth were randomly divided into the following five groups: group 1: intact teeth (control); group 2: inlay preparations, lithium-disilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
44
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 30 publications
(52 reference statements)
9
44
1
Order By: Relevance
“…It is possible that the load applied may not have been challenging enough to fracture the tested specimens. In a study performed by Saridag et al, 26 the mean fracture strength found in molar teeth restored by a lithium-disilicate ceramic inlay was 2646.7 (± 360.4) N. Thus, further studies are warranted to determine the influence of more challenging situations than those applied in the present study, including the use of higher loads, of test groups with non-restored teeth or inlays cemented with non-adhesive cements, and of test groups with the same wall thickness, but with cusp reduction.…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that the load applied may not have been challenging enough to fracture the tested specimens. In a study performed by Saridag et al, 26 the mean fracture strength found in molar teeth restored by a lithium-disilicate ceramic inlay was 2646.7 (± 360.4) N. Thus, further studies are warranted to determine the influence of more challenging situations than those applied in the present study, including the use of higher loads, of test groups with non-restored teeth or inlays cemented with non-adhesive cements, and of test groups with the same wall thickness, but with cusp reduction.…”
Section: Discussionmentioning
confidence: 96%
“…The width and depth of premolar preparations are important factors affecting tooth strength [14, 15]. The type of cavity preparation and materials also affect the extent of tooth fracture [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…[16,19,27] Sarıdag et al reported that cuspal coverage decreased the fracture resistance of the posterior tooth and lithium-disilicate glass-ceramic restoration complex. [28] Researchers also revealed that the teeth restored with zirconia ceramic inlays or onlays demonstrated similar fracture resistance from each other and also to that of intact teeth.…”
Section: Discussionmentioning
confidence: 93%
“…Fracture resistance of inlays and onlays may be influenced by the quantity of the dental structure removed. [28] Hence, in several studies, the fracture strength of the restorative materials for endodontically treated teeth has been evaluated in the inlay cavities without cuspal coverage. [16,19,27] Sarıdag et al reported that cuspal coverage decreased the fracture resistance of the posterior tooth and lithium-disilicate glass-ceramic restoration complex.…”
Section: Discussionmentioning
confidence: 99%